Use of immune modulation by human adipose-derived mesenchymal stem cells to treat experimental arthritis in mice - Zhang, Li (Am J Transl Res, 2017)
Rheumatoid arthritis is a chronic and systemic autoimmune disease characterized by inflammatory cell infiltration and joint erosion. Human adipose-derived mesenchymal stem cells (hASCs) have shown the capacity of suppressing effector T cell activation and inflammatory cytokine expression. We investigated whether hASCs play a therapeutic role in collagen-induced arthritis (CIA) by administering a single dose of hASCs in mice with established CIA. In vivo, a beneficial effect was observed following hASC infusion as shown by a marked decrease in the severity of arthritis. Human ASCs were detectable in the joints, and reduced levels of pro-inflammatory cytokines and increased levels of anti-inflammatory cytokines were observed in the sera of the hASC-treated mice. Furthermore, hASC treatment induced the expansion of regulatory T cells (Tregs) both in the peripheral blood and in the spleen tissues. In vitro, hASCs downregulated the production of proinflammatory cytokines TNF-α, IL-1β, and IL-6 in mouse macrophages stimulated with lipopolysaccharide and inhibited the proliferation of human primary T cells in response to mitogens. Thus hASCs represent a novel and effective therapeutic strategy for RA.